Protective effect of a novel polyherbal formulation on experimentally induced osteoarthritis in a rat model - Orhan, Cemal; Tuzcu, Mehmet; Durmus, Ali Said; Şahin, Nurhan; Ozercan, Ibrahim Hanifi; Deeh, Patrick Brice Defo; Şahin, Kazım (Elsevier France-Editions Scientifiques Medicales Elsevier, 2022)
Osteoarthritis (OA) is a musculoskeletal disorder mainly found in elderly individuals. Modern treatment of OA, like nonsteroidal anti-inflammatory drugs, corticosteroids, hyaluronic acid injections, etc., is linked to long-term side effects. We evaluated the anti-osteoarthritic properties of a novel joint health formula (JHF) containing Bisdemethoxycurcumin enriched curcumin, 3-O-Acetyl-11-keto-beta-Boswellic acid-enriched Boswellia, and Ashwagandha in monosodium iodoacetate (MIA)-induced knee OA in rats. Twenty-eight female rats were distributed into four groups: Control, OA, OA + JHF (100 mg/kg), and OA + JHF (200 mg/kg). JHF decreased the right joint diameters but increased the paw area and stride length compared to the OA group with no treatment. JHF significantly reduced the arthritic conditions after four weeks of supplementation (p < 0.05). JHF significantly decreased TNF-alpha, IL-1 beta, IL-10, COMP, and CRP in the serum of osteoarthritic rats (p < 0.0001). We observed reduced lipid peroxidation but increased SOD, GSH-Px, and CAT activities in response to JHF treatment in OA animals. JHF down-regulated MMP-3, COX-2, and LOX-5 and improved the histological structure of the knee joint of osteoarthritic rats. JHF demonstrated a protective effect against osteoarthritis, possibly due to antiinflammatory and antioxidant activity in experimentally induced osteoarthritis in rats, and could be an effective option in the management of OA.
Keywords: Osteoarthritis; Joint health formula; Pain; Inflammation; Rat